Tradisi Masyarakat Desa Ujan Mas Lama dalam Penghormatan Terhadap Puyang - Wenni Septia Pratiwi; Hudaidah Hudaidah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to describe the beliefs of people in Ujanmas Lama Village towards puyang and the customs carried out to honor them. By using documentation, interviews, and direct observation, this study uses ethnography as a method of data collection. The study shows that the residents of Ujanmas Lama Village interpret puyang as an ancestor or village founder who is respected from generation to generation. Therefore, the community has a strong belief that puyang has supernatural or magical powers that can influence their lives. Everything related to puyang relics is considered sacred and is believed to contain spiritual power, so it must be maintained and respected. This belief is reflected in various traditions that are still carried out today, such as visiting puyang graves, respecting puyang relics, and following customary laws that have been passed down since the puyang era. All of these traditions are real forms of community respect for puyang as an important part of their identity and cultural heritage.